Case Series : Efficacy of Local Infiltration Analgesia with Lidocaine â Epinephrine 0.5% as Post Cesarean Section Pain Management in Kalabahi Public Hospital - Katipana, Madyline Victorya; Alphonso, Aloysius (Bali Journal of Anesthesiology, 2018)
Background: Caesarean section is one of the most commonly performed surgical operations in the world today. Caesarean section commonly induces moderate to severe pain for about 48 hours. It requires optimal perioperative pain management. Postoperative pain management is an important issue in clinic. Proper and efficient pain management is necessary during hospitalization for preventing the related complication which could affect mother and neonate health status. Recently, multimodal pain management has been tested as postoperative pain management. One of the alternatives that can be used is local infiltration analgesia (LIA) method. Local infiltration analgesia technique can provide an adequate effect of analgesia and reduced parenteral opioid consumption without any adverse effects.Case Presentations: Cases in this study collected from Kalabahi Public Hospital, East Nusa Tenggara, Indonesia. 42 patients who met the inclusion criteriaÂ Â  underwent caesarean section was injected with Lidocaine-Epinephrine 0.5% in abdominal muscle and subcutaneous layer as postoperative pain management. After that, the patients were observed to evaluate pain score with Visual Analog Scale (VAS), opioid consumption as the pain rescue, the level of satisfaction, and to evaluate post caesarean wound.Conclusion : This study showed that lidocaine-epinephrine 0.5% injection reduced postoperative pain, so allowed early mobilization and reduced the nurseâsÂ  work, increased the patientâs satisfaction, and there were no report of wound complication. This study also showed the pain score of the first 24 hours was 2.095238 with standard deviation 0.878178, and just 4 patients who asked for rescue analgesic.